2020
DOI: 10.1017/langcog.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

Commitment and communication: Are we committed to what we mean, or what we say?

Abstract: Are communicators perceived as committed to what they actually say (what is explicit), or to what they mean (including what is implicit)? Some research claims that explicit communication leads to a higher attribution of commitment and more accountability than implicit communication. Here we present theoretical arguments and experimental data to the contrary. We present three studies exploring whether the saying–meaning distinction affects commitment attribution in promises, and, crucially, whether commitment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Participants might therefore have treated speakers who only implied to have first-hand evidence in the same way as speakers who explicitly claimed to have such evidence. This finding would be in line with work showing that listeners often take speakers to be committed to their implied meaning (Bonalumi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participants might therefore have treated speakers who only implied to have first-hand evidence in the same way as speakers who explicitly claimed to have such evidence. This finding would be in line with work showing that listeners often take speakers to be committed to their implied meaning (Bonalumi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, Experiments 2 and 3 accounted for this confound between bare assertions and ‘seen’ claims. The results from these experiments suggested that the extent to which such a source claim is made explicit makes a difference in terms of how believable a statement and how accountable for its truth its speaker is taken to be (Bonalumi et al, 2020 ): Our participants’ believability and accountability judgments differentiated between statements they remembered to have been asserted on the basis of first-hand evidence from those remembered to have been asserted on other grounds.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, with weaker implicatures, participants were more likely to select the minimal proposition of the utterance as representative of the explicit content ('what is said'). Consistent with the hypothesis that meaning strength (modulated by relevance) influences accountability and plausible deniability, Bonalumi et al (2020) found that the same explicit broken promise produced different social repercussions for the speaker depending on whether the recipient was known to rely on the promise made by the speaker. Finally, Sternau, Ariel, Giora, & Fein (2015) investigated the deniability of enrichments, as well as weak and strong implicatures using an explicit question about deniability (akin to Reis & Wiegmann, 2021).…”
Section: How Does Meaning Strength Impact Accountability and Plausibl...supporting
confidence: 64%
“…Overall, although enrichments are pragmatic phenomenaand thus cancellablethey are often perceived to contribute to the utterance's truth-conditions and generally appear more difficult to deny than implicatures, which are unarguably part of 'what is implicated'. These two levels of meaning should, therefore, modulate both accountability and plausible deniability differently (as suggested by Bonalumi et al, 2020 andReins &Wiegmann, 2021).…”
Section: How Does the Level Of Meaning Impact Accountability And Plau...mentioning
confidence: 99%
See 1 more Smart Citation